Desenvolvimento de sistemas de liberação controlada de nutrientes agrícolas utilizando polímeros biodegradáveis derivados do glicerol - Pimenta, Igor Fernandes (2016)
In this work, glycerol-derived polymers for controlled release of fertilizers were developed. Such systems aim to minimize fertilizer leaching and avoid groundwater contamination. Thermosetting polyesters were produced by polycondensation of glycerol with citric, adipic and succinic acids, to produce poly(glycerol adipate)-PGA, poly(glycerol citrate)-PGC, poly(glycerol succinate)PGSU, poly(glycerol l adipate -co-citrate) - PGCA, and poly(glycerol citrate cosuccinate) -PGCSU. These polymers with different hydrophobicity de grees were used to encapsulate 0; 2.5; 5; 10, 20 and 40 wt.% KCl. Polymers and polymers/fertilizer were characterized by differential scanning calorimetry (DSC), thermal gravimetric analysis (TGA), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). Results showed that all polymers are amorphous, as expected, and thermally stable up to 200°C.Moreover, depending on the comonomer, polymers were brittle and fragile or rubbery.KCl release studies were performed using UV-Vis spectrophotometry to release times of up to 120 h. Release profiles were dependent on the type of polymer obtained and therefore on its hydrophobicity/hydrophilicity, i.e., the release profile was modulated by the choice of comonomers used. These results indicate that it was possible to develop controlled release systems for fertilizers, adding value to glycerol and modulating profile release by the choice of polymer produced and quantity of the nutrient added.